A qualitative study exploring barriers to adequate uptake of antenatal care in pre-conflict Syria: low cost interventions are needed to address disparities in antenatal care - Rima Mourtada; Hyam Bashour; Fiona Houben (BMC, 2021)
Abstract Background Syria has made progress in reducing maternal mortality and morbidity before the conflict in 2011. Despite the improvement in antenatal care (ANC) coverage and patterns of use, analyses of national surveys demonstrated wide regional variations in uptake, timing and number of visits even after controlling for women's socio-demographic characteristics. This study compares two governorates: Latakia, where uptake of ANC was high and Aleppo, where uptake of ANC was low to highlight the barriers to women's adequate uptake of ANC that existed in Syria pre-conflict. Methods This qualitative study carried out 30 semi-structured interviews with (18-45-year-old) pregnant women from Aleppo and Latakia (recruited purposively from different types of health facilities in rural and urban areas), and 15 observation sessions at health facilities. Transcripts and fieldnotes were analyzed using the Framework Method with attention to the dimensions of availability, accessibility and acceptability of services. Results Inadequate uptake of ANC in Aleppo included not attending ANC, seeking care with providers who are not trained to provide ANC or discontinuing care. Three themes explained the regional disparities in the uptake of ANC in Aleppo and Latakia: women's assessment of their health status and reasoning of causes of ill health in pregnancy; women's evaluation of the risks of seeking ANC; and women's appraisal of the value of different types of service providers. Poor experiences at public health facilities were reported by women in Aleppo but not by women in Latakia. Evaluations of ANC services were connected with the availability, accessibility (geographical and financial) and acceptability of ANC services, however, women's views were shaped by the knowledge and prevailing opinions in their families and community. Conclusions Findings are utilized to discuss low-cost interventions addressing the disparities in ANC uptake. Interventions should aim to enable vulnerable women to make informed decisions focusing on regions of low uptake. Women's groups that foster education and empowerment, which have been effective in other low resource settings, could be of value in Syria. Increased use of mobile phones and social media platforms suggests mobile health technologies (mHealth) may present efficient platforms to deliver these interventions.